Carbon Accounting: A Critical Review of the Accounting Treatment of Carbon Credits as Intangible Assets vs. Inventory - Massagar Al Sya’ban; Yusnaini Yusnaini (GLOBAL SCIENTS PUBLISHER, 2026)
Carbon trading requires transparent carbon accounting practices; however, the absence of established international standards has led to inconsistencies in reporting across companies. This study aims to critically evaluate the accounting treatment of carbon credits, particularly the classification debate between intangible assets (IAS 38) and inventory (IAS 2). Using a Systematic Literature Review (SLR) method on 14 articles, the review results indicate that conceptually, the IAS 38 approach is more appropriate despite challenges in measuring fair value, whereas IAS 2 is more relevant for trading purposes. Analysis through Positive Accounting Theory indicates that management exploits this gap in standards to select accounting policies that benefit the company’s financial position. Therefore, global standardization of carbon accounting is urgently needed to enhance the comparability and accountability of financial statements.